Discovery of thiazostatin D/E using UPLC-HR-MS2-based metabolomics and σ-factor engineering of Actinoplanes sp. SE50/110 - Schlüter, Laura; Hansen, Kine Østnes; Isaksson, Johan; Andersen, Jeanette Hammer; Hansen, Espen Holst; Kalinowski, Jörn; Schneider, Yannik Karl-Heinz (Frontiers in Bioengineering and Biotechnology, 2024)
As the natural producer of acarbose, Actinoplanes sp. SE50/110 has high industrial relevance. Like most actinobacteria, the strain carries several more putative biosynthetic gene clusters (BGCs) to produce further natural products, which are to be discovered. Applying a metabolomics-guided approach, we tentatively identified five further compounds that are produced by the strain: watasemycin, thiazostatin, isopyochelin, pulicatin, and aerugine. Comparison of the genomic context allowed the identification of the putative BGC, which is highly similar to the watasemycin biosynthetic gene cluster of Streptomyces venezuelae. In addition to the identified molecules, a thiazostatin-like compound was found. Isolation and following structure elucidation with 1D, 2D NMR, and HRMS was applied. The fraction containing m/z 369.0929 [M+H] + comprised in fact two highly similar compounds identified as thiazostatin D and thiazostatin E. The compounds possessed the same phenole-thiazole-thiazole molecular scaffold as the previously reported thiazostatin and watasemycin and has anti-proliferative activity against breast adenocarcinoma cell line MCF7 and human melanoma cell line A2058 while no activity again non-malignant immortalized fibroblast cell line MRC-5 was observed. We could further show that manipulation of global transcriptional regulators, with sigH (ACSP50_0507) and anti-anti-σ factor coding ACSP50_0284 as example, enabled the production manipulation of the 2-hydroxyphenylthiazoline family molecules. While manipulation of sigH enabled the shift of peak intensities between the five products of this pathway, ACSP50_0284 manipulation prevented their production. The production of a highly polar compound with m/z 462.1643 [M+H] + and calculated elemental composition C19H27NO12 was activated under the ACSP50_0284 expression and is exclusively produced by the engineered strain.